Existential Angst in Kate Chopin’s The Story of an Hour - Paudel, Kishor (NCC Journal, 2019)
The present article on Kate Chopin’s The Story of an Hour (1894) explores women’s anxieties and struggles for self identity within the arena of strict social and traditional structures deeply rooted in the then American society in the late nineteenth century. Through this short story, Chopin portraits her feminist view and uses her own inspiration for surviving normal life in the mind of the American women for whom existing freely realizing their identity and potentiality had been far cry. Thus, drawing upon the idea of Simone de Beauvoir and other writers, this paper examines the desire and struggle of the female protagonist, Mrs. Mallard for her meaningful existence in the male-dominated society in America.